Self-appraisal of hockey players of high class of different playing position - Oleksiy Mikhnov (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to expose the features of display of self-appraisal for the hockey players of high class of different playing position. Material and Methods: for the exposure of level of self-appraisal for hockey players, information of sportsmen of high class, taking part in the matches of the Kontinental hockey league (KHL) in a season 2013-2014 was probed sixteen hockey players, having a sporting digit MS and MSWC, took part in researches. Methods were used: pedagogical supervision, pedagogical analysis and generalization of front-rank experience, psychological testing, analysis of data of the special scientific-methodical literature, expert questioning, an analysis of data is the Internet. Results: findings allowed to set that the players of line of attack (central and extreme forward) have more high level of self-appraisal for certain, than players of defence and hockey goalkeepers. This tendency is looked over both on the separate constituents of self-appraisal and on the whole on all spectrums of the studied indexes. The got results of researches rotined that the hockey players of high class had or middle or high level of self-appraisal. Among testable hockey players, players were not exposed with the low level of self-appraisal. Conclusions: the exposed distinctions in the level of self-appraisal of hockey players of high class can be used for diagnostics of playing predisposition and choice of playing line of business in a command.